XaxAB‐like binary toxin from Photorhabdus luminescens exhibits both insecticidal activity and cytotoxicity. Issue 1 (22nd November 2013) - Zhang, Xu; Hu, Xiaofeng; Li, Yusheng; Ding, Xuezhi; Yang, Qi; Sun, Yunjun; Yu, Ziquan; Xia, Liqiu; Hu, Shengbiao
Abstract The enterobacterium Photorhabdus luminescens produces a number of toxins to kill its insect host. By analyzing the genomic sequence of P. luminescens TT01, we found that amino acid sequences encoded by plu1961 and plu1962 showed high similarity to XaxAB binary toxin of Xenorhabuds nematophila, which has both necrotic and apoptotic activities in both insect and mammalian cells in vitro. To evaluate the biological activity of Plu1961/Plu1962, their coding genes were cloned and expressed in Escherichia coli. Both Plu1961 and Plu1962 were expressed as soluble protein in BL21 (DE3) and their mixture caused insect midgut CF‐203 cells death via necrosis. Confocal fluorescence microscopy showed that Plu1961/Plu1962 mixture was able to depolymerize microtubule and induce the increase in plasma membrane permeabilization in CF‐203 cells. Moreover, co‐expression of Plu1961/Plu1962 in the same cytoplasm exhibited cytotoxic effect against mammalian cells (B16, 4T1, and HeLa cells) and injectable activity against Spodoptera exigua larvae. Until now, two types of binary toxins have been identified in P. luminescens, the first type is PirAB and Plu1961/Plu1962 is the second one. The biological role of Plu1961/Plu1962 binary toxin played in the infection process should attract more attention in future.